An Analysis of Parallel Education Systems in Pakistan, and the Challenges They Pose in Education Research - Malik, Muhammad Abid; Hassan, Rukhsana (Advances in Social Sciences Research Journal, 2015)
Education system in Pakistan is complex. Unlike most of the other education systems in the world which can easily be divided on the basis of urban and rural, or public and private; Pakistan also has parallel education systems with their own distinctive, sometimes contrasting curriculum, teaching methodologies, examination systems, education culture and boards/ organizations that regulate and conduct exams in them. Although there are many, the most important ones are government boards affiliated (leading to SSC- Secondary School Certificate- and HSSC- Higher Secondary School Certificate), deeni madaris/ religious schools (either working independently or controlled by independent boards/ waqfs) and British Council affiliated schools (leading to GCE- General Certificate of Education/ GCSE -General Certificate of Secondary Education). Although many other countries in the world also have parallel education systems, their numbers and influence is not as high as in Pakistan. The presence of these systems also causes confusions in the findings of the research as the findings of one education system is taken as the finding of all. In some cases, the data is also mixed, causing confusions with findings. This papers looks at the parallel education systems in Pakistan, their spread, characteristics, merits and demerits. It also looks at the possible challenges and confusions that such education systems can cause in educatin research. It also suggests ways to help overcome the challenges.